GAME-BASED LEARNING FOR SUPPLY CHAIN MANAGEMENT: DESIGN AND IMPLEMENTATION OF PRODUCTION AND DISTRIBUTION GAME - Kurniawan, Ivan; Sutikno, Jehoshapat; Pratama, Aditya Tirta (EDUCATE : Jurnal Teknologi Pendidikan, 2026)
Supply chain management is one of the most complex systems, requiring deep understanding of interconnected processes, decision-making, and dynamic in-teractions. This study presents the design and evaluation of game-based learning to enhance higher education students’ comprehension of supply chain management. The proposed game is named production and distribution game which represent interactive simulation that represents key supply chain element including material and information flows, costing, and coordination among users. The study involves 40 undergraduate Industrial Engineering students enrolled in a logistics and supply chain management course between 2025-2026. Following the session, a survey that based on six points Likert-scale was given to evaluate the engagement and effectiveness of the game. The results revealed a high mean-scores ranging from 4.025 to 4.975 indicating positive student perception towards the learning activity. The findings demonstrate that game-based learning can improve student engagement, motivation, and conceptual comprehension. In additional, the game-based learning approach also provides a more interactive and experiential learning environment for logistics and supply chain education.